Os ciclos do cuidado: costurando olhares sobre a relação entre avós e netos - Cavalcante, Mohana Ellen Brito Morais (2022)
This thesis work is the result of a study started in 2016 during the Master's Degree in Sociology where I researched with and about teenage mothers, their babies and grandparents. It therefore aims to add to this investigation, but with greater theoretical and empirical depth. The present study seeks to analyze the relationships between different generations, grandparents and grandchildren, considering aspects such as moral and cultural values, affections and particularities of each generation, in order to understand the construction of symbolic bonds between these family members. My investigation enters the field of ―close grandmothers‖, those who cohabit or live with their grandchildren on a daily basis. The research sought to identify, based on the perception of those involved, the influence of the childhood experienced by the grandmothers on the childhood lived by their grandchildren and co-experienced by them. Grandmothers and great-grandmothers take care of their grandchildren along with the care of their parents, so none of them was fully responsible for their granddaughter (o), therefore, I analyzed a conviviality, essentialized in the care given by wanting to take care and by the needs of different natures of the children, the parents and grandparents and great-grandparents.The investigative path passed through discussions of childhood, generation and care in family contexts. From the theoretical-methodological point of view, the study is based on the empirical analysis of experiences constituted by children who are students of a public day care center in the city of João Pessoa-PB and ten families from Paraíba. I start from a perspective of qualitative analysis, considering the listening of the subjects, my main source of information, I did it from the participant observation and in conversations via Google Meet and Whatspp. It concludes that grandmothers practice avoternity when taking care of their grandchildren, however, trying not to replace this doing with the mother's doing, seeking not to appropriate the place of motherhood motherhood, legal guardian, biological bond. It was also observed that care can be found at both ends, children also take care of their grandmothers as they are cared for, children and grandmothers ―look‖ at each other.The presence of other family caregivers of the children was evidenced, therefore, the child is assumed to belong to the cohabiting family, family members who live together have some degree of commitment in caring for the infant. I looked at a dynamic established between these subjects that reverberates in something similar to a cycle, which moves in order to turn the person cared for into a future caregiver. The study took on the challenge that implies the deepening of a dialogue between Sociology and Anthropology, overcoming dichotomies between the Social Sciences and enabling a more complete analysis of what I called Family Cycles of caring and serving.Finally, I draw attention to the fact that the thesis research was crossed by the Covid 19 pandemic, mainly during the years 2020 to 2021, so that I specified this fact in the text, with regard to the methods used, profile of employees and results achieved.